Possible associations between plasma fibroblast growth factor 21 levels and cognition in bipolar disorder - Favour Omileke; Sayuri Ishiwata; Junko Matsuo; Fuyuko Yoshida; Shinsuke Hidese; Kotaro Hattori; Hiroshi Kunugi (Wiley, 2020)
Abstract Bipolar disorder (BD) is a mental disorder characterized by extreme changes in mood polarity. It is also characterized by cognitive and metabolic dysfunctions. Fibroblast growth factor 21 (FGF21) is an endocrine protein that has a multifaceted function such as glucose and lipid regulation in the periphery, and neuroprotection and induction of synaptic plasticity in the central nervous system. Previous studies reported inconsistent results concerning peripheral FGF21 levels in patients with BD. In this study, we compared plasma FGF21 levels between 26 patients with BD and 51 healthy controls using a human FGF21 ELISA Kit. There was no significant difference in plasma FGF21 levels between the patients and controls. We found significant positive correlations between plasma FGF21 levels and some cognitive parameters (word association and motor speed). If our results are replicated that higher peripheral FGF21 may be associated with better cognitive performance in patients with BD.